The Challenges of Diverse Workforce & Inclusive Culture in Hospitality Operation – A Multilevel Analysis of Pakistan - Abbas, Saman Fatima (Digital Repository of Theses - SSBM Geneva, 2025)
This research study examines the challenges and enablers of managing workforce diversity and building inclusive organizational cultures in Pakistan’s hospitality sector. Employing a qualitative comparative -case design, the research uses a three-phase multilevel approach: document review and observation to map current D&I policies and practices; two-tier semi-structured interviews with senior decision-makers (CEOs/owners) and with HR directors and operational team leads to capture intent and implementation realities; and systematic thematic analysis grounded in Saxena’s seven diversity variables and Hofstede’s six cultural dimensions. Findings reveal persistent policy–practice gaps, structural and cultural barriers to inclusion, and implementation bottlenecks in recruitment, career progression, communication, and training systems. At the same time, leadership commitment, targeted talent pipelines, and structured language and communication initiatives emerge as practical enablers. The study concludes with actionable recommendations for policy alignment, co, inclusive HR processes, trainings and leadership development. This research study recognizes a fact that a contextually adapted, multilevel strategy is essential to convert workforce diversity into sustainable competitive advantage. The results offer a practical roadmap for hospitality managers in Pakistan and a basis for further research on Diversity and Inclusion in emerging-market service industries especially in Asia.